The Right to Exclude Others from Private Property: A Fundamental Constitutional Right - David L. Callies; J. David Breemer (Washington University Journal of Law & Policy, 2000)
This Essay discusses the fundamental nature of the right to exclude as it emanates not only from decisions of the U.S. Supreme Court but from selected federal circuit and state appellate court decisions. As appears below, the right to exclude applies to both government and private activity on private land, whether the activity is the result of governmental attempts to secure a public interest or of theories associated with stronger rights emanating from custom and public trust.
Keywords: Land use; Property rights